Analisis Kontaminasi Logam Berat dan Mikroba Pada Gula Aren Sesuai Standar Pangan Indonesia di Pusat Produksi Desa Menggala Lombok Utara - Dwining Elfriede; Yalun Arifin; Natasya Aprilia (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
Palm sugar is widely produced in the North Lombok region, but the production process is still conventional. Consequently, the probability of metal contamination and microbial contamination is very high. This study aims to assign the safety characteristics of palm sugar in Menggala Village, North Lombok, in guaranteeing public health by analyzing the possible contamination. The requirements of factors are based on SNI 3743-2021 for metal contamination and SNI 7388:2009 for microbial contamination. This study used samples from Menggala Village, North Lombok, in November 2021. Samples were taken from one batch of the final product at the production house center, as much as 2 kg from 5 kg of total production. Heavy metal content was analyzed using AAS and ICP-OES. Analysis of Total Viable Count (TVC) and Total Yeast and Mold Count (TYMC) used the pour-plate TPC method, while the coliform test was analyzed using the Most Probable Number (MPN) method. The results of heavy metal contamination meet the SNI 3743:2021 standard. So, the palm sugar is free from these. The results of the TVC and TYMC meet the SNI 7388:2009 standard. However, the palm sugar does not meet the established criteria of SNI 7388:2009 for coliforms. The amount of presence above the threshold is the possible presence of pathogenic microbes that are harmful to human health. The cleanliness factor is the main factor causing the high value of coliform analysis. Several recommendations can be implemented, namely improving hygiene and sanitation facilities for workers, maintaining worker hygiene such as washing hands before and after processing, going to the toilet, handling dirty materials, and wearing clean clothes with head coverings, gloves, masks, or work shoes. Training and education programs are required, and incentives for workers to comply with these standards.